2011
DOI: 10.4049/jimmunol.1100092
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between IL-18 and IL-18 Receptor Limits the Magnitude of Protective Immunity and Enhances Pathogenic Responses following Infection with Intracellular Bacteria

Abstract: The binding of IL-18 to IL-18Rα induces both pro-inflammatory and protective functions during infection, depending on the context in which it occurs. IL-18 is highly expressed in the liver of wild type (WT) C57BL/6 mice following lethal infection with highly virulent Ixodes Ovatus Ehrlichia (IOE), an obligate intracellular bacterium that causes acute fatal toxic shock-like syndrome. In this study, we found that IOE infection of IL-18Rα-/- mice resulted in significantly less host cell apoptosis, decreased hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 73 publications
(125 reference statements)
4
44
0
Order By: Relevance
“…Alternatively, PR3 might induce the secretion of mature IL-18 by activating protease-activated receptor 2 [47]. In a series of studies, IL-18R and NK cells have been shown to play a pathologic role in lethal systemic infection with Ixodes ovatus ehrlichia, a Gram-negative obligate intracellular bacterium [33,48]. The studies have shown that either IL-18R deficiency or depletion of NK cells leads to higher resistance to this pathogen, reduced liver injury, and lower IL-10 production as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PR3 might induce the secretion of mature IL-18 by activating protease-activated receptor 2 [47]. In a series of studies, IL-18R and NK cells have been shown to play a pathologic role in lethal systemic infection with Ixodes ovatus ehrlichia, a Gram-negative obligate intracellular bacterium [33,48]. The studies have shown that either IL-18R deficiency or depletion of NK cells leads to higher resistance to this pathogen, reduced liver injury, and lower IL-10 production as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…At this time point, chicks infected with SG had clinical signs of FT and more severe histopathological changes than those infected with SG Fla + , suggesting that IL-18 over-expression could be related to the severity of disease. IL-18 promotes inflammation and enhances CD8 + T lymphocyte proliferation and cytotoxic activity (Eckmann and Kagnoff, 2001;Raupach et al, 2006;Ghose et al, 2011).…”
Section: Article In Pressmentioning
confidence: 99%
“…However, failure to remove apoptotic neutrophils resulted in sustained inflammation (23)(24)(25)(26). Studies have demonstrated that elevated levels of Ccr1 during bacterial peritonitis and sepsis were associated with neutrophil accumulation and severe pathology while Ccr1 deficiency decreased neutrophil accumulation and abrogated inflammation and pathology in a murine model of kidney injury and inflammation (27), suggesting that neutrophils play a pathogenic role in sepsis.…”
Section: Th1 Cells T Helper 17 (Th17) Cells and Cd8mentioning
confidence: 99%
“…Our previous study indicated that NKT cells play a dual role during lethal Ehrlichia infection. While IFN-␥ production by NKT cells is essential for effective intracellular bacterial clearance, they also promote infection-induced toxic shock syndrome (27,30,31). In contrast, NK cells play a detrimental role during fatal ehrlichiosis as they inhibit protective anti-Ehrlichia immunity and mediate tissue injury during fatal disease (29,31,32).…”
Section: Changes In Myeloid Cell Populations Following Lethal Ehrlichmentioning
confidence: 99%